Liberal Education in the Global Perspective - Peterson, Patti (International Higher Education, 2011)
Though graduate education at research universities has been emphasized since the late 19th century, liberal education for undergraduates is still alive in Western countries, including the US, and is developing in non-Western countries. In the curricular reform of non-Western countries, the understanding of the fundamental purpose of liberal arts education, preparing students with broad intellectual skills for life and transferable analytical skills for the workplace, will be necessary.